Deskripsi Kualitas Air Pada Mata Air Permandian Matakidi Sebagai Air Minum - La Ode Sahamada; La Harudu; Surdin; Sitti Kasmiati (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Barangka Village is a place that has a water source that has a large discharge so that it is able to supply water needs as drinking water. The objectives of this study are: 1) to determine the physical quality of water such as temperature, turbidity, color, odor, and taste; and 2) to determine the chemical quality of water such as pH, salinity, detergent content of Matakidi bathing springs as drinking water in Barangka Village, Barangka District, West Muna Regency. This type of research is a descriptive survey research. The data analysis technique used in this study is comparative data analysis. The results of this study indicate that the average physical quality includes temperature 25.8oC, turbidity 5 NTU, color 11.2 TCU, odorless and tasteless. While the chemical quality includes pH 7.28, salinity 0.02 ppt and detergent content 0.24 mg/l. Based on the research results, it can be concluded that the physical and chemical properties of the Matakidi Bathing Spring that do not meet the standard requirements for drinking water are the detergent content because it exceeds the maximum limit that has been determined, namely 0.05 mg/l based on the Regulation of the Minister of Health of the Republic of Indonesia No. 492/Menkes/Per/IV/2010.